Modified insulated punnets and conventional packaging films for retail storage of robusta banana fruits - Abdul-Rahaman, Adams; Pasenaa Peter, Abdul-Wahab Salifu, Leori Inusah and (Journal of Scientific Agriculture, 2017)
The application of poor consumer packaging technology to Banana fruits can increase fruit susceptibility to diseases which affect quality and shelf-life. Understanding the use of appropriate consumer packages is crucial in developing packages for the fresh produce sector. In this study, four different consumer packages and Control Samples (CT) which included Perforated Insulated Punnet (PP), Non-perforated Punnet (NP), Perforated Films (PF) and Non-perforated Films (NF) were used. Fruits in packages were stored at 27°C for 7 days where rate of ripening, weight loss, total soluble solids, taste, pulp texture and consumer acceptance were assessed. The results demonstrated that the use of perforated punnets was better in reducing the rate of ripening. The changes in TSS was progressive in all the treatments but the control sample produced the highest Brix at 16% compared with Brix 15% for fruits in PP, NP. PF and NF. Weight loss was more pronounced in the control sample 11.7% compared with the least weight loss of 0.7% for fruits in NF. Except, Sweetness and TSS without dilution all the parameters assessed were statistically significant at P ≤ 0.05. Based on the results obtained in this research, it can be shown that the use of insulation and perforations of punnets demonstrated appropriateness which offers a promise and can be adopted for consumer use in the fresh produce sector.